Secondary Extramedullary Myeloma of the Gallbladder: A Case Report. (August 2022) - Kolagatla, Sandhya; Jenkins, Joshua K.; Strunk, Haley; Smith, Forrest; Ganti, Subramanya Shyam; Moka, Nagabhishek
Extramedullary myeloma (EMM) is an infrequent but well-established manifestation of multiple myeloma (MM), defined as a soft tissue plasma cell neoplasm without bone marrow involvement. Gallbladder involvement in EMM, however, is a very rare occurrence, with only 8 cases found in the English medical literature. Here, we present a case of an older adult male with a gallbladder mass in the presence of increasing serum kappa light chains after a normal bone marrow biopsy confirmed the complete remission of a previous MM diagnosis. Histopathologic evaluation of a biopsied sample confirmed the mass as an atypical plasma cell neoplasm. Later in his treatment, he developed several firm, smooth, violaceous skin nodules on the torso, which histopathology confirmed as also being atypical plasma cell neoplasms. We aim to contribute to the medical literature by expanding the pool of information regarding EMM of the gallbladder to support future diagnostic and treatment recommendations.